![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có: \(B=1+2^2+2^4+.....+2^{18}\)
\(\Rightarrow2B=2+2^3+2^5+...+2^{19}\)
\(\Rightarrow2B-B=\left(2+2^3+2^5+....+2^{19}\right)-\left(1+2^2+2^4+...+2^{18}\right)\)
\(\Rightarrow B=2^{19}-1\)
Vậy rút gọn biểu thức \(B=1+2^2+2^4+...+2^{18}\) được \(2^{19}-1\)
B =1+2^2+2^4+2^6+...+2^18
=2^0+2^2+2^4+2^6+...+2^18
4B=2^2+2^4+2^6+2^8+...+2^20
4B-B=(2^2+2^4+2^6+2^8+...+2^20)-(2^0+2^2+2^4+2^6+...+2^18)
3B=2^2+2^4+2^6+2^8+...+2^20-2^0-2^2-2^4-2^6-...-2^18
3B=2^20-2^0
3B=2^20-1
B=(2^20-1)/3
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)
\(A=\frac{6^3+3.6^3+3^3}{-13}=\frac{3^3.2^3+3^3.2^2+3^3}{-13}=\frac{3^3\left(8+4+1\right)}{-13}=\frac{27.13}{-13}=-27\)
b)
A=1+5+52+53+...+550
5A=5+52+53+...551
5A-A=(5+52+53+...+551)-(1+5+52+...+550)
4A=551-1
A=\(\frac{5^{51}-1}{4}\)
c)
A=2100-299+298-...+22-2
2A=2101-2100+299-...+23-22
2A+A=(2101-2100+...+23-22)+(2100-299+...+22-2)
3A=2101-2
A=\(\frac{2^{101}-2}{3}\)
b.
\(A=1+5+5^2+5^3+...+5^{49}+5^{50}\)
\(5A=5+5^2+5^3+...+5^{50}+5^{51}\)
\(5A-A=\left(5+5^2+5^3+...+5^{50}+5^{51}\right)-\left(1+5+5^2+..+5^{50}\right)\)
\(4A=5^{51}-1\)
\(A=\frac{5^{51}-1}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a,71.2-6.(2x+5)=10^5:10^3
142-6.(2x+5)=10^2
142-6.(2x+5)=100
6.(2x+5)=142-100
6.(2x+5)=42
2x+5=42:6
2x+5=7
2x=7-5
2x=2
x=1
Vậy x=1
47.34.96 : 613
=47.(34.36.36):613
=47.316:613